Design Science Research Contributions: Finding a Balance between Artifact and Theory - Richard Baskerville; Abayomi Baiyere; Shirley Gregor; Alan Hevner; Matti Rossi (Association for Information Systems, 2025)
With the rising interest in Design Science Research (DSR), it is crucial to engage in the ongoing debate on what constitutes an  acceptable  contribution for publishing DSR - the design artifact, the design theory, or both. In this editorial, we provide some constructive guidance across different positioning statements with actionable recommendations for DSR authors and reviewers. We expect  this  editorial  to serve as a foundational step towards clarifying misconceptions about DSR contributions and to pave the way for the acceptance of more DSR papers to top IS journals